2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.25633
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students’ Learning in Statics Skills: Using Homework and Exam Wrappers to Strengthen Self-regulated Learning

Abstract: Statics is one of the fundamental courses required for engineering students, particularly for students in the mechanical, civil and aerospace fields. This course introduces students to modeling and solving real-world systems, including drawing Free Body Diagrams (FBD) and setting up equilibrium equations. These two skills are critical for bridging introductory courses to more advanced courses, such as Dynamics, Mechanics of Materials and others. The process of teaching these foundational skills typically invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 7 publications
(9 reference statements)
1
25
0
2
Order By: Relevance
“…These reflective or metacognitive questions are optionally selected by the instructor. Our initial results agree with those that have found that while students are very positive on having immediate feedback, the reflective/metacognitive questions, while important to student learning, tend to be less popular 17,18,19 .…”
Section: Example 1 -Filling a Weigh Tanksupporting
confidence: 90%
“…These reflective or metacognitive questions are optionally selected by the instructor. Our initial results agree with those that have found that while students are very positive on having immediate feedback, the reflective/metacognitive questions, while important to student learning, tend to be less popular 17,18,19 .…”
Section: Example 1 -Filling a Weigh Tanksupporting
confidence: 90%
“…As previously discussed, quantitative and qualitative results collected from wrappers usually reflect on the mutual benefits to both students and the teaching team to improve and enhance the served education [4]. The significance of the results of this study lies within the ability of assessing exam-wrappers in general (to what extinct was this tool useful), and its impact in MECH393 in specific (was it helpful in terms of improving students' performance).…”
Section: Significance Of the Results Obtainedmentioning
confidence: 77%
“…Exam-wrappers can be defined as structured reflection activities in which students engage in after their instructor marks and returns an exam [3]. Previous studies showed that using exam-wrappers, in particular, is an excellent method of assessing student performance, metacognitive skills, and study behaviors [4], [5]. Such studies have further shown that wrappers have a huge impact on students' learning outcomes.…”
Section: Motivation For the Papermentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions include assignments where students write about their problem solving processes (Hanson, 2008;Goldberg, 2015;Goldberg, 2016), exam wrappers (Chen, 2016;Chew, 2016), assignment correction opportunities (Chen 2016), and surveys of study habits (Grohs, 2015).…”
Section: Motivationmentioning
confidence: 99%